1991
DOI: 10.1103/physrevb.44.6558
|View full text |Cite
|
Sign up to set email alerts
|

Theory of magnetic and structural ordering in iron clusters

Abstract: The structural properties of neutral iron clusters Fe"(n~4) are investigated using a first-principles, all-electron, linear-combination-of-Gaussian-orbitals method. The ground states are all ferromagnetic with highest-dimensional geometry. They exhibit a tendency toward enhanced bond length, narrower d-band widths, and maximum pairs of nearest-neighbor bonds. Such conditions are favorable for maximizing the energy gain for ferromagnetism, thereby stabilizing the ground-state geometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
64
2
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(87 citation statements)
references
References 24 publications
19
64
2
2
Order By: Relevance
“…One observes that the inter atomic distances follow the trends in the atomic radii as in the case of dimers. For Fe 3 , the lowest energy structure is an equilateral triangle with bond length 2.19 Å , in good agreement with previous DFT studies, which have reported bond lengths of 2.15, 2.37, 2.04, 2.10 and 2.11 Å (Chen et al 1991;Gong and Zheng 1995;Castro and Salahub 1994;Oda et al 1998;Ballone and Jones 1995) respectively. Compared to Fe 2 , the bond length shows a tendency to increase, indicating that the system always favors the highest dimension for longer bond length.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…One observes that the inter atomic distances follow the trends in the atomic radii as in the case of dimers. For Fe 3 , the lowest energy structure is an equilateral triangle with bond length 2.19 Å , in good agreement with previous DFT studies, which have reported bond lengths of 2.15, 2.37, 2.04, 2.10 and 2.11 Å (Chen et al 1991;Gong and Zheng 1995;Castro and Salahub 1994;Oda et al 1998;Ballone and Jones 1995) respectively. Compared to Fe 2 , the bond length shows a tendency to increase, indicating that the system always favors the highest dimension for longer bond length.…”
Section: Resultssupporting
confidence: 79%
“…The Fe-Fe bond length, 2.00 Å , is in consistent with the experimental values 1.87 Å (Montano and Shenoy 1980) and 2.02 Å (Purdum et al 1982) obtained in different studies and theoretical results of Gong Appl Nanosci (2014) 4:593-600 595 and Zheng (1995), which has shown a bond length of 2.09 Å . However, the calculated bond length is considerably smaller than the nearest neighbor distance, 2.48 Å in bulk bcc Fe (Kittel 2008 (Chen et al 1991;Oda et al 1998;Ballone and Jones 1995), and is in keeping with the value obtained in experiments (3.3 ± 0.5) (Cox et al 1985). For the pure Fe and Ir dimers, the local and average magnetic moments are equal and it indicates that the spin density,…”
Section: Resultsmentioning
confidence: 49%
See 2 more Smart Citations
“…DFT calculations are known to describe structural and vibrational properties very accurately. 39,40 Several DFT calculations have been done on bare Fe clusters, including up to seven atoms, [41][42][43][44] but we are not aware of calculations on hydrogenated clusters. For the Fe n H m clusters studied here, precise structures are not known and the size of these clusters prevents an extensive search of cluster configurations using firstprinciples calculations to find the minimum energy structures.…”
Section: B Infrared Photodissociation Spectramentioning
confidence: 99%